The Use Animation Movie on Whatsapp Group to Improve Students' Narrative Writing Skills - Reza Intan Pandini; Ngasbun Egar; Theresia Cicik Shopia (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
The goal of this study was to explore if using animated movies may help students in grade XI SMK Bhakti Husada Brebes improve their ability to write narrative prose. Because most students lack a strong vocabulary, they struggle to choose appropriate words while writing narrative prose; as a result, they rely on media to help them improve their writing. The purpose of this study at Grade XI SMK Bhakti Husada Brebes was to report students' achievement in narrative text writing ability and students' activities in the learning process utilizing Animation Movie. To acquire data, this study used quantitative research and a quasi-experimental study design. In 2021/2022, the population of SMK Bhakti Husada Brebes' study class XI students. The researcher used two courses as control and experiment classes, XI Farmasi as the control and XI Perawat as the experiment. The researcher employed two sorts of instrument tests, pre-test and post-test, to collect data. A Folded Wish, an animated film, was employed by the researcher. The findings demonstrated that training students' writing skills using video can improve their capacity to create narrative text, as seen by a rise in mean scores. The students' pre-test score in the control group was 59,00, but it increased to 68,73 after the test. In experiment class, the students' pre-test score was 54,43, which increased to 80,10. It is conceivable to deduce that the second cycle's mean score was higher than the first cycle's mean score. Furthermore, the pupils improved and became more active and enthusiastic in the learning process, as evidenced by observation notes.